Designing a Population Information System at the Siaro-Aro Walinagari Office Using the Java Netbeans 8.0.2 Programming Language: Perancangan Sistem Informasi Kependudukan Pada Kantor Walinagari Siaro-Aro Menggunakan Bahasa Pemograman Java Netbeans 8.0.2 - Jeprimansyah Jeprimansyah; Tri Monarita Johan; Yulhan Yulhan; Edwin Anwar; Febriyanno Suryana (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
The recording and processing of population data is the responsibility of the Regency/City government, where the implementation starts from the kelurahan/nagari as the spearhead of government. The nagari / kelurahan government is responsible for the process of data collection and population administration, for further recapitulation of population data to be reported to the level II regional government, in this case the City / Regency civil registry office. These services need to be done quickly and accurately to get information. In recording and processing population data which is currently running, the Nagari Siaro – Aro government has used computer aids. However, the computer applications used in these agencies have not been fully able to support the performance of the mayor's office equipment in providing excellent public services and in accordance with the principles, principles and standards of public services that are simple, fast, responsive and accurate as well as effective and efficient to the community. This is because the application used for processing population data in the mayor's office is still classified as a simple application such as Microsoft Office.